Social Media Application for FSKTM Students (FSKTMConnect) - See, Hong Chen; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2025)
Social media is a useful tool for discovering latest information. Students use social media for their social lives and academic purposes. However, it is noticeable that students at Faculty of Computer Science and Information Technology (FSKTM), Universiti Tun Hussein Onn Malaysia (UTHM) lack a centralized hub for convenient access to academic and campus information. Therefore, Social Media Application for FSKTM Students (FSKTMConnect) is developed to provide a common platform for students to access and exchange academic and campus information. Waterfall software deveploment life cycle and a full-stack development tool called “MERN” are utilized to develop the application. The application is developed using web-based approach that allows students to access the application through desktop or mobile. This application will provide a common platform for student to access latest academic and campus information At the end, this application is expected to foster a stronger sense of community within UTHM.